Determinación del costo del servicio de internet bajo Metodología ABC en La Empresa Adnet S.A.S. (2024)
ABC costing is a costing method that assigns indirect costs to products or services based on their activity consumption. This method is more accurate than traditional methods, such as volume costing, because it takes into account the complexity of the services and resources consumed, for this reason knowing its importance within a company, it was decided to apply this costing method to the company ADNET S.A.S in order to know the economic reality of it, to implement strategies which improve the margins of costs and expenses acquired at the time of providing the different services offered by the company.